Application of a bilateral temporal fascia free graft in a dog with multifragmented frontal sinus and nasal bone fracture. Issue 6 (15th March 2022) - Dunand, Lucile; Belluzzi, Elena; Bongartz, Alexandre; Caraty, Johan
Abstract: Objective: To describe the use of temporal fascia free grafts to treat dorsal open comminuted frontal sinus and nasal fractures. Animal: One Belgian shepherd dog. Study design: Case report Methods: A 5‐year‐old spayed female Belgian shepherd was admitted with severe facial deformation due to trauma. A deep, 3 cm wide wound was present between the nose and the frontal sinus. No abnormalities were detected on neurological examination. On computed tomographic examination, comminuted open fractures of the frontal and nasal bones were associated with a severe depression of the dorsal wall and presence of bone fragments in the sinus cavities. Bone fragments were apposed with polydioxanone monofilament suture. Bilateral temporal fascia grafts were placed over the bone fragments. Results: The integrity of the frontal and nasal cavities, and the facial profile of the dog were restored. No short‐term or long‐term complications were observed after 4 months follow up. Conclusion: The innovative combination of suture apposition of bone fragments and a temporal fascia free graft resulted in very satisfying long‐term outcomes in a dog with open sinus and nasal bone fractures.